Performance and Kinetics of the Treating Slaughterhouses Wastewater Using Sequencing Batch Reactor - Warodomrungsimun, Chaowalit; Patthanaissaranukool, Withida; Buayoungyuen, Surussinee; Fongsatitkul, Prayoon (Asian Health, Science and Technology Reports, 2019)
This research investigated the processes of simultaneous biological removal of organic carbon, nitrogen, and phosphorus from slaughterhouse wastewater and determined the bio-kinetics of the organic carbon and nutrient removal process under long sludge age (solids retention time 60 days) using a sequencing batch reactor (SBR). The reactor processed the wastewater by varying the solids retention times (SRTs) (10, 20, 30 and 60 days) under a 12 h cycle, which included a 0.5 h anaerobic static fill period and a 0.5 h settle period, while the remaining reaction time consisted of Anoxic I/Oxic I/Anoxic II/Oxic II (1.5/2.5/2.5/1.5 h). The result of the cyclic study revealed that the majority of the chemical oxygen demand (COD) removal occurred in the first anoxic period with the reaction of the denitrification process and the anaerobic phosphorus release process. The concentration of total kjeldahl nitrogen (TKN) in the reactors decreased, and the percentage of oxidation was greater than 80%, at the end of oxic I period. The resulting biomass composition was that the VSS/SS ratio, at 60 days SRT, was lower than at the 30 days SRT. The fraction of PHA (fPHA) at the 60 days SRT was lower than at 30 days SRT. Prior to the study of the kinetics parameters, sensitivity analysis was conducted to evaluate the most important parameters. The results of the sensitivity analysis showed that the µH,S, ηNO2, ηNO3, kSTO, YH,S, and YH,STO had an influence on the denitrification process, and the µAOB, µNOB, YAOB and YNOB had an influence on the nitrification process. Also, the qPO4, qPP, YPHA, Kmax,PAO had an influence on the biological phosphorus removal. The result of kinetic parameter estimation of qPHA, YPO4, qPP, and YPHA were 1.33 day-1, 0.18 mgP/mg COD, 0.13 day-1, and 0.19, mgP/mg COD, respectively. The results of the kinetics studies and evaluation of the systems performance can be used to justify the operational and design for the effectiveness of SBR.